2011
DOI: 10.1152/ajpheart.00172.2011
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic α3β2-nAChRs mediate cerebral neurogenic nitrergic vasodilation in the swine

Abstract: Lee RH, Liu YQ, Chen PY, Liu CH, Chen MF, Lin HW, Kuo JS, Premkumar LS, Lee TJ. Sympathetic ␣3␤2-nAChRs mediate cerebral neurogenic nitrergic vasodilation in the swine. Am J Physiol Heart Circ Physiol 301: H344 -H354, 2011. First published May 2, 2011; doi:10.1152/ajpheart.00172.2011.-The ␣7-nicotinic ACh receptor (␣7-nAChR) on sympathetic neurons innervating basilar arteries of pigs crossed bred between Landrace and Yorkshire (LY) is known to mediate nicotine-induced, ␤-amyloid (A␤)-sensitive nitrergic neurog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 50 publications
(79 reference statements)
1
30
0
Order By: Relevance
“…It is possible that the concentration of increased released norepinephrine in the synapse is below that capable of significantly activating the β 2 -adrenoceptors and mediated neurogenic vasodilation, or the enhanced vasodilation is overcome by their possible direct α-adrenoceptor-mediated smooth muscle constriction effects (Easton et al, 2007). This latter suggestion in the basilar arteries is excluded, since porcine basilar arteries are endowed, from functional aspect, predominant β 1 -adrenoceptors (Lee et al, , 2011. Furthermore, the threshold concentration of these agonists (N 30 μM) for a direct constriction of smooth muscle was significantly higher than that for their inhibition of nicotine-induced vasorelaxations (our preliminary results).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that the concentration of increased released norepinephrine in the synapse is below that capable of significantly activating the β 2 -adrenoceptors and mediated neurogenic vasodilation, or the enhanced vasodilation is overcome by their possible direct α-adrenoceptor-mediated smooth muscle constriction effects (Easton et al, 2007). This latter suggestion in the basilar arteries is excluded, since porcine basilar arteries are endowed, from functional aspect, predominant β 1 -adrenoceptors (Lee et al, , 2011. Furthermore, the threshold concentration of these agonists (N 30 μM) for a direct constriction of smooth muscle was significantly higher than that for their inhibition of nicotine-induced vasorelaxations (our preliminary results).…”
Section: Discussionmentioning
confidence: 99%
“…The cerebral perivascular sympathetic nerves originate in the SCG (Lee et al, 2011). To elucidate whether ketamine and methamphetamine blocked native nAChRs, effects of these drugs on nicotine-induced inward currents in dissociated rat SCG neurons were examined.…”
Section: The Nachrs-mediated Inward Currents Were Reduced By Ketaminementioning
confidence: 99%
See 1 more Smart Citation
“…With proper timing and dosage, administration of PAME and SAME can be a successful therapy against cerebral ischemia. Lin et al (2008) first reported that PAME released from SCG (the largest cervical ganglion in the sympathetic tract (Lee et al, 2011a(Lee et al, , 2011bLee et al, 2012;Wu et al, 2014)) is a novel vasodilator (Lin et al, 2008). Exogenous application of PAME directly onto the rabbit or rat thoracic aorta induced vasodilation in a concentration-dependent manner (Lin et al, 2008;Lee et al, 2010;Lee et al, 2011c).…”
Section: Fatty Acidsmentioning
confidence: 99%
“…All blockade by these different substances and inhibitors in normal animals is due to inhibition of nAChRs and is prevented by statins (Si et al 2005, Mozayan et al 2006, Mozayan & Lee 2007) and oestrogen (Si et al 2011) but not by testosterone (Lee et al 2011b). The blockade by b-amyloid peptides, however, is dependent on the subtypes of nAChR in that a7-nAChR but not a3b2-nAChR is sensitive to b-amyloid peptides (Si & Lee 2002, Lee et al 2011a, although both types of receptors are sensitive to cholinesterase inhibitors and mediate sympatheticparasympathetic interaction mechanism in inducing cerebral nitrergic vasodilation (Lee et al 2011b).…”
mentioning
confidence: 99%